Yeasts: Genomics, biotechnology and health benefits - Tanasupawat, Somboon; Kingkaew, Engkarat (My University, 2024)
Yeast, with its roots in taxonomy and ecology, has become a crucial element in modern biotechnology. It offers profound insights into genetic diversity and ecological roles. This book explores yeast's lasting importance and its significant impact across various scientific disciplines and societal contexts. Yeast serves as a catalyst for scientific innovation and contributes to sustainable advancements in biotechnology and beyond. The importance of yeast is multifaceted. In taxonomy and ecology, yeast is vital for understanding industrial yeast taxonomy, distribution, and ecological adaptations. Genomic analysis of yeast provides critical insights, with practical applications such as astaxanthin production. In biotechnology, yeast is essential for producing alcoholic beverages. It is involved in traditional fermentation processes and the sensory complexities of these beverages. Yeast also offers potential health benefits associated with moderate alcohol consumption and has a significant influence on Asian alcoholic beverages. Additionally, yeast plays a crucial role in the production of amino acids, lipid synthesis for biofuels and cosmetics, and the use of yeast beta-glucan in cosmeceuticals. Yeast significantly contributes to health-focused foods by providing nutritional benefits in bread and baking and acting as probiotics in fermented foods. Its role is especially notable in Japanese fermented foods. In agriculture, yeast is used in animal feed additives and demonstrates biocontrol potential. Its bioactive compounds effectively mitigate plant diseases and enhance crop yield, highlighting its importance in sustainable agricultural practices.